DINAMIKA DALAM PRAKTIK PERNIKAHAN: TAWARAN UNTUK MENGURANGI PREVALENSI POLIGAMI DI ERA KONTEMPORER - Arif Sugitanata; Suud Sarim Karimullah; Faradila Hasan (STAI Sufyan Tsauri Majenang, 2024)
This research addresses the complex debate regarding the practice of polygamy, which is a hot and controversial topic in various social, religious, legal, and personal contexts around the world. This research focuses on the history, relevance, and solutions of polygamy practices in the contemporary era. This study, conducted through qualitative research, details the history of polygamous practices from historical, cultural, and religious perspectives. The research questions raised include aspects of how the practice of polygamy developed, whether it is considered a necessity or a lifestyle in the contemporary era, and how solutions can be applied to overcome the negative impacts of the practice. The results show that the practice of polygamy has a long and complex history relating to historical, cultural, and religious factors. In the contemporary era, polygamy is still debated with a multifaceted approach. The research proposes solutions involving public education on gender equality and human rights, strengthening laws and policies that support monogamy, promoting intercultural and interfaith dialogue, women's economic empowerment, and developing socialisation programmes. Psychological support, public policies in favour of monogamous families, and the building of community support networks are also considered important in curbing the practice of polygamy. This research contributes to a better understanding of the dynamics of polygamous practices by combining historical analyses, contemporary studies, and relevant solutions. The results reflect the complexity of interactions between religion, culture, law, and individual choice in the contexts where polygamy is practised. Efforts to reduce the prevalence of polygamy not only rely on enforcing social norms but also involve building solid foundations for healthy and egalitarian relationships and families in the contemporary era.